Peptide Drugs: Current Status and it's Applications in the Treatment of Various Diseases - Chandarana, Chandni; Juwarwala, Isha; Shetty, Shravi; Bose, Anushree (Current Drug Research Reviews, 2024)
Peptides represent a class of natural molecules with diverse physiological functions, including hormone regulation, neurotransmission, and immune modulation. In recent years, peptide- based therapeutics have gained significant attention in pharmaceutical research and development due to their high specificity, efficacy, and relatively low toxicity. This review provides an overview of the current landscape of peptide drug development, highlighting the challenges faced in their formulation and delivery and the innovative strategies employed to overcome these hurdles. The review explores the wide range of applications of peptide drugs in treating various diseases, including HIV, multiple sclerosis, osteoporosis, chronic pain, diabetes, and cancer. Examples of FDA-approved peptide drugs and ongoing clinical trials are presented, showcasing the continuous advancements in peptide-based therapeutics across different therapeutic areas. This review underscores the promising potential of peptide drugs as targeted and effective treatments for a multitude of medical conditions, offering improved therapeutic outcomes and enhanced patient care.
Keywords: Peptide drugs